The 1957 Valencia flood: hydrological and sedimentological reconstruction and comparison to the current situation - C. Puertes; F. Francés (Ingeniería del Agua)
This work aims to improve the knowledge of the flood that took place in Valencia, Spain, in 1957. In other words, the aim is to test if it is possible to explain the flood waves with the incorporation of sediment cycle to a distributed hydrological model. Furthermore, this work aims to be aware of the current consequences of a similar event, taking into account land use changes, particularly, the urban rise in the lower basin, and the current flood defenses of the city. To do this, the hydrological model was implemented in the current basin situation. Once implemented, a reconstruction of precipitation at hourly discretization for the 1957 event was made and the sedimentological sub-model was calibrated. Then, the hydrographs in the chosen points were obtained. Finally, a simulation using the 1957 precipitation in the current basin situation was made, in order to be aware of the current consequences.